Identification of Pseudocercospora mori as the causal agent of grey leaf spot disease in mulberry (Morus atropurpurea) from various localities in Guangdong Province, China - Qazi, Izhar Hyder; Yuan, Ting; Liu, Xi; Liu, Jiping (Frontiers in Plant Science, 2025)
During periods of high temperature and humidity, mulberry trees become susceptible to fungal leaf spot disease, which can significantly reduce both the yield and quality of their leaves. In this study, we collected samples of mulberry leaf spot disease from six regions of Guangdong province of China. The disease samples were studied using traditional morphological methods, high-throughput sequencing technology, molecular phylogenetic analysis, and pathogenicity tests. The observed morphological features of the pathogen were consistent with those of Pseudocercospora. High-throughput sequencing results revealed the presence of multiple fungal species in the samples, with Pseudocercospora spp. comprising the highest proportion. The complete rDNA and mitochondrial genome sequences of Pseudocercospora spp. were assembled. Based on the sequencing data, primers were designed to amplify and sequence barcode gene regions, including ITS, Cyt b, and COI. Phylogenetic analyses consistently placed the pathogen within the family Mycosphaerellaceae. ITS-based identification confirmed the pathogen as a member of the genus Pseudocercospora, while the Cyt b and COI sequences indicated a relatively distant relationship with the closely related genus Cercospora, thereby supporting the morphological classification of the pathogen at the molecular level. In addition, pathogenicity validation identified Pseudocercospora mori as a primary causal pathogen of leaf spot disease in mulberry. PCR primers specifically designed based on the rDNA sequence of Pseudocercospora mori achieved a detection sensitivity as low as 3 × 10⁻² ng/μL. In conclusion, based on morphological and molecular phylogenetic evidence, we identified Pseudocercospora mori as the causal pathogen of mulberry leaf spot disease. This study provides useful data for practical management of mulberry leaf spot disease at the field level, aiding in the sustainable development of sericulture.